Drying of apricots in a rotary column cylindrical dryer (RCCD) supported with solar energy - Sarsilmaz, C; Yildiz, C; Pehlivan, D (Pergamon-Elsevier Science Ltd, 2000)
Rapid deterioration of fruits and vegetables necessitates their consumption in a limited area. The solutions to this problem may be provided by technological precautions, which not only increase economic efficiency but also motivates agricultural developments. Among the technological operations applied to increase the market life of the foods, drying operation is of prime importance which is applicable to almost all the agricultural products, In this work, drying of apricots in a newly developed rotary column cylindrical dryer (RCCD) equipped with a specially designed air solar collector (ASC) was investigated to find optimum drying air rate and rotation speed of dryer, to maintain uniform and hygienic drying conditions and to reduce drying times. For this purpose, the changes in the moisture contents of the Sugarpiece (Sekerpare) foods were studied. Drying is an operation of prime importance used for almost all the agricultural products. Type apricots dried in the present dryer were compared to those of the same type apricots dried open on the ground. It was shown that co-operation of RCCD and ASC increased drying rate, reduced drying times and rotation of drying chamber provided gains in both time and labour. (C) 2000 Elsevier Science Ltd. All rights reserved.
Keywords: Dehydration; Carrots